Geomorphology Of Yogyakarta Area And Its Surrounding Proposed As A Geomorphological Field Laboratory - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACT This paper introduces geomorphological conditions of the Yogyakarta area and its surrounding, eventbough in relatively, small area we can fund the complexities and completeness of the geomorphological aspects such as morphology, morphogenetic, morphochronology and morphoarrangement as well. Almost all of the genetic. geomorphological units exist, exep glacial origin. The geomorphological land classification closely relate to the phisical environment components of the area such as topography, soil, hydrology (especially the groundwater) and land use/land cover. The geomorphological land classification also reflect natural hazard occuring in the area such as flood, drought, erosion, massmovement and volcanic (nue ardente and lahars flow). Beginners to study geomorphology are easy to find out samples in the field for identification and classification of the landfinm units of various origin, geomorphic processes (active and dynamic) and the environmental context. Based on the completeness of geomorphological phenomena, Yogyakarta area and its surrounding are promissible as an training, area (fteld laboratory) for students from geography, physical geography, geomorphology and other earth sciences as well